A Survey on the Effectiveness of Online Listening Classes during the Covid-19 Pandemic at English Department of Universitas Riau - Putri, Dita Aulia; Daud, Afrianto; Eliwarti, Eliwarti (Indonesian Journal of Economics, Social, and Humanities, 2023)
This paper discusses a study that focuses on discussing the effectiveness of online learning for students of the English Education Study Program in learning Listening Comprehension 3 courses in online learning. This research is a quantitative descriptive study involving 118 English Department students taking the Listening Comprehension 3 subject at the Universitas Riau. The sample was selected through total sampling technique, in which the entire population that filled out the questionnaire was sampled in this study. Data was collected from a set of questionnaire which were distributed online in the form of a Google Form. The questionnaire was designed using a Likert Scale and documentation in the form of student achievement from the Listening Comprehension 3 subject to support the research results. The results showed that the learning effectiveness of students of the English Department was high with a total average of 3.70 when studying Listening Comprehension 3 in online learning. In conclusion, the effectiveness of online listening classes during the Covid-19 pandemic at the English Department at the University of Riau was high.